Mechanism and regeneration of sulfur-poisoned Mn-promoted calcined NiAl hydrotalcite-like compounds for C3H6-SCR of NO. Issue 7 (22nd January 2020) - Zhao, Ling; Kang, Mengdi
Abstract : The selective catalytic reduction of NO with propene (C3 H6 -SCR) in the presence of SO2 was investigated over a series of Mn-promoted calcined NiAl hydrotalcite-like compounds. Abstract : The selective catalytic reduction of NO with propene (C3 H6 -SCR) in the presence of SO2 was investigated over a series of Mn-promoted calcined NiAl hydrotalcite-like compounds. The obtained 5% MnNiAlO catalyst exhibits superior NO conversion efficiency (95%) at 240 °C, and excellent sulfur-poisoning resistance. The possible reaction pathways of the catalytic process were proposed according to several characterization measurements. It is demonstrated that Mn-promoted NiAlO catalysts enhance the Brønsted acid sites and surface active oxygen groups, and improve the redox properties by the redox cycle (Ni 3+ + Mn 2+ ↔ Ni 2+ + Mn 4+ ). Thus, the amount of the reaction intermediates is improved, and the reactivities between C x H y O z species and nitrite/nitrate species are promoted. Furthermore, in the presence of SO2, the MnNiAlO samples can give rise to minor formation of sulfate and inhibit the competitive adsorption effectively due to their nitrite/nitrate species being more abundant and stable. Finally, regeneration was studied using in situ FTIR and the water washing method showed the best performance on the regeneration of S-poisoned catalysts.